Feed Supplementation with Encapsulated Indigenous Probiotic Lactic Acid Bacteria Increased Broiler Chicken Performance - Pradipta, Monica Sonia Indri; Harimurti, Sri; Widodo, Widodo (ASEAN Journal on Science and Technology for Development, 2019)
The oral application of probiotics in the poultry industry is time-consuming and laborious. Therefore, using a powdered probiotic supplement that can easily mix with feed is important. We investigated the effect of spray drying encapsulation on the viability of indigenous probiotic lactic acid bacteria during production and storage and evaluated broiler chicken performance after providing the supplement. Encapsulated probiotics exhibited >80% survival rates after spray drying. All bacterial species maintained up to 80% cell viability rates after exposure to 80–85°C temperatures for 15 or 30 s. The viable cell number of all encapsulated bacteria decreased over seven weeks of storage. The supplement was mixed with feed at concentrations 0.5 (T1), 1.0 (T2), and 1.5 (T3) g/kg feed and administered to 48 one-day-old Lohmann broiler chickens for 21 days; a T0 group was raised without probiotic supplementation. Probiotic supplementation affected body weight gain, live weight, and feed conversion ratio. The cecum length and duodenum and cecum weights significantly differed among the treatment groups. Probiotic supplementation was associated with improved villus development in the intestinal epithelium compared with that of the control. Thus, feed supplementation with indigenous probiotic powder stimulates intestinal epithelial proliferation in broiler chickens during the starter phase, improving their performance.